Species distribution and clinical profiles of coagulase-negative staphylococci (CoNS) isolated from blood cultures among paediatric patients in Hospital Kuala Lumpur - Masri, Siti Norbaya; Wan Abu Bakar, Wan Nazirah; Ibrahim, Rosni; Noh, Mohamed Asyraf; Nawi, Salbiah (Malaysian Medical Association, 2020)
Introduction: Coagulase-negative staphylococci (CoNS) is often considered as a culture contaminants but it can potentially be pathogenic to patients with risk factors. A combination of species identification and clinical criteria has been suggested in determining true CoNS bacteraemia.